The Efficacy of Heat-Clearing (Qingre) and Detoxifying (Jiedu) Traditional Chinese Medicine Gargle for Chemotherapy-Induced Oral Mucositis: A Systematic Review and Meta-Analysis - Lin, Zhixian; Chen, Jiangfeng; Han, Sunya (Frontiers in Pharmacology, 2021)
Objective: Chemotherapy-induced oral mucositis (CIOM) is an extremely serious complication of cancer. In China, the heat-clearing (Qingre) and detoxifying (Jiedu) traditional Chinese medicine QRJD-TCM gargle has been widely used to treat CIOM. To date, no systematic evaluation has been conducted on the clinical efficacy of QRJD-TCM gargle in treating CIOM. The objective of this systematic review and meta-analysis was to evaluate the efficacy of QRJD-TCM gargle in the treatment of CIOM. Methods: Relevant randomized controlled trials (RCTs) comparing QRJD-TCM gargle with conventional Western medicine mouthwash (CWMM) for CIOM were confirmed by systematically searching PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, Chinese Scientific Journal Database, Wanfang Database, and Sinomed until October 20, 2020. Two researchers independently assessed the risk of bias according to the Cochrane risk-of-bias criteria. Excel 2010 was used in setting up a database of extracted information, and RevMan 5.3.0 was used in analyzing included trial data. The composition of the QRJD-TCM gargle was evaluated. Results: A total of 25 articles were included in this meta-analysis. Results showed that compared with CWMM, QRJD-TCM gargle can reduce the incidence of CIOM (OR = 0.23, 95% CI [0.18, 0.29], p < 0.00001) and severity of CIOM (grade I–II: OR = 0.36, 95%CI [0.28, 0.46], p < 0.00001; grade III–IV: OR = 0.15, 95%CI [0.09, 0.28], p < 0.00001). In addition, QRJD-TCM gargle improved the effective rate of CIOM (OR = 15.91, 95% CI [7.93, 31.89], p < 0.00001). Conclusion: QRJD-TCM gargle is effective in preventing and treating CIOM. However, more standard, double-blind, and multicenter randomized controlled studies are needed to further confirm the efficacy of QRJD-TCM gargle in the prevention and treatment of CIOM.